EM biofertilizer and organic fertilizer co-application modulate vegetation-soil-bacteria interaction networks in artificial grasslands of alpine mining regions - Lyu, Liangyu; Shi, Jianjun; Gao, Pei; Cai, Zongcheng; Li, Fayi (Frontiers in Microbiology, 2025)
To address vegetation establishment challenges caused by poor soil in the alpine mining areas of the Qinghai–Tibet Plateau. Through three-year field experiments, this study systematically investigated the effects of combined EM microbial fertilizer and organic fertilizer application on vegetation community characteristics, soil physicochemical properties, and bacterial community diversity/functional structure in artificial grasslands of alpine mining areas. Key findings include: (1) The synergistic treatment of EM biofertilizer and organic fertilizer significantly improved the physical and chemical properties of soil and the characteristics of vegetation community. The Y2E2 treatment consistently enhanced vegetation community characteristics and soil physicochemical metrics in 2023 and 2024. Compared to the control (CK), it increased soil total nitrogen (TN) by 68.92 and 76.31%, reduced pH by 8.31 and 11.11%, and boosted biomass by 75.97 and 84.02%, confirming its efficacy in alleviating nutrient stress and promoting plant growth. (2) Microbiome analysis revealed that biofertilizer treatments significantly improved soil bacterial community structure. The Y2E2 and Y2E3 showed the highest OTU numbers (2,481 and 2,501 respectively). The Y2E3 increased relative abundance of Actinomycetota (+18.2%) and Acidobacteria (+12.7%) compared to CK (organic fertilizer 0.00 kg m−2 + EM biofertilizer 0.00 kg m−2), while reducing Pseudomonadota (−14.3%). The Y2E2 improved Shannon (2.36%), Ace (6.44%), and Chao1 (5.05%) indices versus CK. Y1E1 exhibited 67.11% positive correlations in microbial co-occurrence networks. (3) Environmental drivers and functional activation: Mantel tests and RDA revealed soil electrical conductivity (SEC) and pH were negatively correlated with bacterial diversity indices (except Simpson). Other soil physical and chemical indexes and plant community indexes are positively correlated with soil bacterial diversity index except Simpson index. Soil pH emerged as the key driver of bacterial community construction. Combined fertilization neutralized alkalinity, activated manganese-oxidizing and photosynthetic microbes, while excessive application triggered heterotroph competition. In summary, the combined application of EM microbial fertilizer and organic fertilizer accelerates biomass accumulation in plant communities by regulating soil pH and improving the structure, function, and diversity of soil bacterial communities. These ecological processes involving plant-soil-microbe interactions expedite the restoration of ecological functions in artificial grasslands within alpine mining areas. Among the treatments, Y2E2 demonstrated the best performance, with an application rate of 600.00 kg of EM biofertilizer per hectare combined with 20.00 tons of organic fertilizer.